Le Jardin du Trocadéro : un arboretum dans le parc de Saint-Cloud - Pauline Choulet (Les Cahiers de l'École du Louvre)
The English garden of the Trocadéro was created in 1824 because Louis XVIII wanted a private park for the royal children. From its creation, there was a desire to turn it into a real arboretum: it was planted with numerous species of rare and exotic trees and shrubs. Moreover, the principles governing the composition of the Trocadéro garden corresponded to those set out in the treatises of the first half of the nineteenth century concerning the composition of paths, plant masses, viewpoints, colours and movement. During the Second Empire, it underwent major modifications, including the creation of a lake, to bring it into line with the taste of the time. This was the last major modification of the garden because, since the second half of the twentieth century, there have been no long-term maintenance projects; they are carried out piecemeal. However, many remarkable species still make up the Trocadero, which retains its function as an arboretum.